Triethylamine inhibits influenza A virus infection and growth via mechanisms independent of viral neuraminidase and RNA-dependent RNA polymerase. - Masaki Shoji; Kensuke Nakaoka; Momiji Ishikawa; Yusuke Kasai; Tomoyuki Esumi; Etsuhisa Takahashi; Hiroshi Kido; Hiroshi Imawaga; Takashi Kuzuhara (PLoS ONE)
Triethylamine (Et3N) is a proton (H⁺) acceptor that is widely used in various industrial organic synthesis processes, including the production of pharmaceuticals, agrochemicals, and polymers. Inhalation of high Et3N concentrations can damage human respiratory tract and lungs. Given the compound's known reactivity and membrane-penetrating properties, we hypothesized that non-toxic concentrations of Et₃N may exert modulatory effects on virus-host interactions in epithelial cells. We thus investigated the anti-influenza activity of Et3N and found that it enhanced the viability of influenza A H1N1 and H3N2 virus-infected Madin-Darby canine kidney (MDCK) cells. Non-cytotoxic Et3N concentrations reduced the number of infected cells and suppressed influenza A virus nucleoprotein expression as well as viral gene and antiviral host gene upregulation in infected MDCK cells. Selectivity index values of Et₃N against influenza A virus infection, ranging from approximately 10 to over 50. These findings indicated that Et3N inhibited influenza A H1N1 and H3N2 viral infections. Additionally, Et3N suppressed influenza A H1N1 and H3N2 virus titers in the infected MDCK cell culture supernatant, suggesting that it inhibited viral growth in infected cells. This implies that Et3N may suppress influenza A virus release and/or replication by targeting viral or host cell factors. However, Et3N did not inhibit influenza A viral neuraminidase or RNA-dependent RNA polymerase activity, which are involved in viral release and replication, respectively. These results suggest that Et3N targets other viral proteins or host cell factors essential for influenza A virus growth. Our findings demonstrate that Et3N exerts anti-influenza activity, providing new insights into the development of antiviral agents based on Et3N skeleton.